UTILIZING VIDEOCAST: FOSTERING STUDENTS’ LISTENING COMPREHENSION - Muhammad Syahruddin Nawir (ETERNAL (English, Teaching, Learning and Research Journal), 2020)
Listening has an important role in communication which is applied in foreign language classroom and it is considered as necessary skill because it has an essential role in facilitating learners to master English proficiency. The aims of this research were to find out the extent to which videocast improves listening comprehension of the fourth semester students of Makassar Islamic University and the students’ perceptions toward the utilization of videocast in teaching and learning activities. This research was carried out in the fourth semester students of English Department of Makassar Islamic University. The method used was quasi-experimental design with pre-test, eight meetings of treatment, and post-test. The data were collected using two kinds of research instruments: listening test and questionnaire. The data were then analyzed by means of statistical analysis through the independent sample t-test and the frequency of questionnaire. The result showed that the independent t-test which compared the students’ score on post-test revealed a value of p<0.05. It means there is a significant difference between listening comprehension of the students who were taught by utilizing videocast and the students who were not taught by utilizing videocast. Furthermore, the analysis of questionnaire indicated that the students’ perceptions toward the utilization of videocast were very positive. It can be concluded that utilizing videocast improves significantly students’ listening comprehension.